Ivan Adrianovich Mikhailov in emigration in Harbin - M. V. Krotova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the unknown pages of the life of Ivan Adrianovich Mikhailov, the Minister of Finance of the Omsk government, during his emigration to China. In Harbin, he spent 25 years of his life, but his activities during this period are almost unknown and surrounded by secrets and rumors. The purpose of the work is to try to get closer to the understanding of this mysterious person on the basis of unpublished archival documents and to clarify some details of his biography. Particular emphasis is placed on his close environment in Harbin, relations with the Japanese, his political views